A Strategic Plan to Develop the Community Outreach Hub at UNEMI, Ecuador - Espinoza-Solís, Eduardo (2021)
The Universidad Estatal de Milagro (UNEMI) is a key higher education institution in the development of region 5 in Ecuador. Therefore, a community outreach strategic plan has been developed; it interrelates all university’s careers and the teaching and research substantive functions. The methodology is executed through a plan based on the university’s domains, the research lines that promote the outreach, the international, national, and local development objectives with which programs and projects were created to increase the impact and coverage in the territory, and the dissemination of the results obtained. As a result, the plan offers strategies of alliances with communities to develop joint actions, support from the private sector to increase resources, which are limited in the public sector, and alliances with other universities in the region to develop joint projects to facilitate the beneficiaries’ field of action through a synergy of massive action.